Avenue Tree Health Survey of Forest Research Institute, Dehradun - Tamang, Kalzen Dolma; Dudhraj, Ankita; Kumari, Anuradha; Pandey, Amit; Kumar, Manoj Kuma (Indian Forester, 2018)
Avenue trees are ornamental, shade giving, aesthetically soothing and may also be medicinally important. Therefore, knowledge of status of tree health in a given area is a pre-requisite in evolving a disease management strategy for the region. Individual trees of the selected roads in the FRI campus were examined for signs and symptoms of different diseases. Tree diseases and their occurrence were calculated. A total of 853 trees were surveyed. 52% trees were diseased which include both exotic and native tree species. It was recorded that trees with girth 150-432 cm were found to be highly affected with pathogenic attack. Decaying trees bearing fruit bodies of pathogens and anthropogenic activities were responsible for disease prevalence. Suitable management strategies have been suggested to address the disease problems on the avenue trees in the FRI campus.